Clinical Characteristics and Prognosis of Patients With Pulmonary Mucoepidermoid Carcinoma: A SEER-Based Analysis - Qiu, Lingxiao; Song, Pan; Chen, Pingmei; Wang, Huaqi; Li, Fangfang; Shu, Mengxuan; Gong, Gen-cheng; Song, Xiangjin; Huang, Chun; Jia, Hongxia; Li, Nana; Zhang, Guojun (Frontiers in Oncology, 2021)
Background: Pulmonary mucinous epidermoid carcinoma (PMEC) is an extremely rare malignancy. Its clinical characteristics and prognosis haven’t been fully understood so far. This study was to evaluate the clinical characteristics and prognostic factors of PMEC, as well as to establish a nomogram to predict its 1-, 3-, 5- and 10-year cancer-specific survival (CSS) rates. Methods: Within the Surveillance, Epidemiology, and End Results Database from its inception to December 31, 2016, patients pathologically diagnosed with PMEC were identified. Kaplan–Meier analysis and Cox regression were performed to evaluate the CSS stratified by different covariates. A predictive model of nomograms was built and validated by the Concordance index (C-index) and calibration curves. Results: A total of 585 PMEC patients were identified. 408 (70%) of them were divided into the training cohort and 177 (30%) patients in the validation cohort. The 5-, and 10-year CSS rates of stage Ⅰ-Ⅱ PMEC patients were 91.4% and 88.9%, respectively. The 1-, 3- and 5-year CSS of stage Ⅲ-Ⅳ PMEC were 56.5%, 39.45% and 32.1%, respectively. The survival curves showed that patients with elderly ages, large tumor size, poor differentiation and high TNM stage were associated with significantly poor prognosis. The CSS outcomes were significantly improved in patients receiving surgical treatments (surgical alone, surgery plus radiation and/or chemotherapy). Patients with radiation and/or chemotherapy had the worst prognosis. The multivariate COX results revealed that the covariates, including age, tumor laterality, tumor sizes, pathological differentiation, lymph node metastasis, distant metastasis, TNM stage and therapy, were independent prognosis factors for PMEC. These factors were used to construct a nomogram. The C-index of the nomogram was 0.921. The calibration curve presented favorable consistency between the predicted CSS and the actual observation. This nomogram was validated by the validation cohort. The C-index of validation cohort was 0.968. Conclusion: Age, bilateral tumor, tumor sizes, pathological differentiation grade, lymph node metastasis, distant metastasis, TNM stage and therapy were independent prognosis factors of PMEC patients. A nomogram on predicting the CSS of PMEC was first built and validated showing its potential value in practice.